The horses are the first thought but one must not forget the zebras even if they are rare: Stiff person syndrome associated with malignant mesothelioma. (7th April 2014) - Koca, Irfan; Ucar, Mehmet; Kalender, Mehmet Emin; Alkan, Samet
Abstract : Stiff person syndrome (SPS) is a rare condition that causes rigidity in the muscles of the body and extremities, difficulty in walking, episodic spasms and progressive disability. SPS is generally seen together with autoimmune disorders such as diabetes mellitus, thyroiditis, vitiligo and pernicious anaemia. Rarely, it may develop as a paraneoplastic condition. SPS cases associated with breast cancer, small cell lung carcinoma, thymoma, Hodgkin's lymphoma and colorectal cancer have been reported in the literature. We present a case of a 58-year-old female patient who had malignant mesothelioma-associated SPS. Patients who have muscle spasms and difficulty in movement of joints should be evaluated for SPS before diagnosis of Parkinson's or other neurological disorders, and possible underlying malignancies should be excluded.